A free-standing CeO2/Co3O4 nanowires electrode featuring a controllable discharge/charge product evolution route with enhanced catalytic performance for Li-O2 batteries. (June 2020) - Wang, Yu; Wang, Jun; Mohamed, Zeinab; Huang, Qishun; Chen, Tingting; Hou, Yuyang; Dang, Feng; Zhang, Weibin; Wang, Hongchao
Graphical abstract: A controlled discharge/charge evolution route based on CeO2 /Co3 O4 hybrid composite was applied to enhance the electrocatalytic performance of free-standing electrode for LOBs. Ultra-long stable cycle durability (500 cycles at 500 mA g −1 ) with low overpotentials (0.2 V (ORR) and 1.0 V (OER) after 500 cycles) was achieved. Highlights: A controlled discharge/charge evolution route based on CeO2 /Co3 O4 hybrid composite. Directly observed the oriented nucleation of Li2 O2 on embedded CeO2 phase as predicted. Characterized the morphology, surface composition and nucleation-growth evolutions of ORR/OER products during cycling. Ultra-long stable cycle durability of 500 cycles at 500 mA g −1 was achieved. Abstract: Although transition metal oxides are important potential catalytic cathode materials for Li-O2 batteries (LOBs), their poor cycle durability at high current density, high overpotentials and side reaction are still the challenges to solve. Herein, CeO2 /Co3 O4 nanowire arrays grown on Ni foam were fabricated as a free standing cathode of LOBs, featuring a controllable discharge/charge products evolution route. CeO2 served as active sites for nucleation, initial growth and decomposition of Li2 O2 . The embedded CeO2 nanocrystalline on Co3 O4 substrate dominated the initial discharge/charge product evolution with multi-formation kinetics of crystal Li2 O2 and Li2-x O2 at high current densities which leading to low overpotentials and efficient decomposition of discharge products. Owing to the stable structure, the CeO2 /Co3 O4 nanowires were found to energetically favor the mass transport between the electrode/electrolyte interface during long cycle testing. As a consequence, excellent cyclability of 500 cycles at high current density (500 mA g −1 ) under a fixed capacity of 500 mA h g −1 with low overpotentials of 0.2 V and 1.0 V for discharge/charge process (after 500 cycles) were achieved. The present work provides a new strategy and intrinsic insight in designing high-performance metal oxides electrocatalysts with a fine-tuned structure for LOBs.